Pyroclastic material from the Puyehue-Cordon-Caulle Volcanic Complex, Chile, as carrier of Beauveria bassiana conidia: Potential utilization in mycoinsecticide formulations - Schalamuk, Santiago (2014)
Fil: Schalamuk, Santiago. Universidad Nacional de La Plata. Centro de Química Inorgánica; Argentina